The Potential of the Blue Economy in Pakistan: Prospects and Challenges - Ayub, Awais (Journal of Pakistan Administration, 2024)
The economy plays a vital role in the progress and prosperity of any nation. Economic growth is essential for executing any human development initiative, including education, health, skill and capacity building, food security, trade, industry, environment, and climate protection or for undertaking measures to ensure internal security and external defense. Pakistan has been facing economic challenges recently, with shrinking exports and increasing imports further complicating our financial and economic woes. Due to heavy reliance on imports of raw materials and higher business costs, our conventional industries are facing a competitive disadvantage. Given these tough situations, Pakistan must explore other avenues for economic turnaround. One such avenue is the blue economy, which remains underutilized in Pakistan despite its massive potential. The country has immense blue reserves in the form of fisheries, seafood, aqua tourism, long pristine beaches, water sports and adventures avenues, captivating islands, renewable power generation potential, offshore oil and gas reserves, shipbreaking and recycling, three seaports with road networks to connect with different regions like Central Asia as well as world’s two largest populations China and India. Besides the vast potential of economic dividends, the blue economy also has relevance due to growing concerns about the climate cost of brown growth. Blue growth is considered an effective model for sustainable growth. The UNO’s Sustainable Development Goals (SDGs 2015) also underline the significance of oceanic reserves for development. SDG 14 is specifically about the sustainable use of blue reserves, while other SDGs, particularly 1, 7, 8, and 9, are also connected.
Keywords: blue economy; exclusive economic zone; maritime affairs